Implementation of Project-Based Learning in the Psychomotoric Development of Primary School Age Students - Zahro Br Sembiring, Ulfa; Nazwa Sidadolog, Rahel (International Journal of Students Education, 2023)
The project-based learning model is a variation of learning that involves project work with teacher management carried out by students. This learning requires deeper thinking because the student’s task is to create a work. Psychomotor is related to actions and skills. This study aims to describe the application of project-based learning which is adapted to activities that hone students’ skills according to the age of elementary school development. In this learning method, the teacher acts as a guide. Project-based learning aims to find solutions to problems. Apart from that, students also learn the concept of problem solving and develop critical thinking skills. Learning critical thinking concepts and skills, students work together in groups to consider real-world problems. It is hoped that learning by applying this learning method can help students be more active and creative, learning from what they see in their environment.